2017
DOI: 10.3390/en10060745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Recycling on the Performance of a Moving Bed Temperature-Swing (MBTSA) Process for CO2 Capture in a Coal Fired Power Plant Context

Abstract: A mathematical model of a continuous moving-bed temperature-swing adsorption (MBTSA) process for post-combustion CO 2 capture in a coal-fired power plant context has been developed. Process simulations have been done using single component isotherms and measured gas diffusion parameters of an activated carbon adsorbent. While a simple process configuration with no gas re-circulation gives quite low capture rate and CO 2 purity, 86% and 65%, respectively, more advanced process configurations where some of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…It is reported that coal's share of the global primary energy consumption is 28.1% in 2016 [1]. However, the emission of CO 2 generated by coal-fired power plants is one of the most important factors leading to global warming [2][3][4]. In order to reduce the emission of CO 2 , strategies need to be devised.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that coal's share of the global primary energy consumption is 28.1% in 2016 [1]. However, the emission of CO 2 generated by coal-fired power plants is one of the most important factors leading to global warming [2][3][4]. In order to reduce the emission of CO 2 , strategies need to be devised.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature swing adsorption based on a moving bed is often used in the field of flue gas cleaning by CO 2 -capture and shows an acceptable effectiveness [1]. The recently proposed TSA-system [2] by the authors of this work for biogas upgrading uses fluidized bed technology in order to achieve higher heat transfer rates compared to fixed or moving beds [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…h FB = h pc + h gc + h rad (1) The particle convection describes the conducted heat transfer from the particle to the surface between a thin remaining gas layer. In most gas-solids fluidized beds, the particle convection is predominat [15].…”
Section: Introductionmentioning
confidence: 99%
“…At GHGT-13 we presented a simplified assessment of the MBTSA process in the Natural Gas Combined Cycle (NGCC) context (Grande et al, 2017). More recently we have carried out a more comprehensive study of the MBTSA process using the composite model approach in gPROMS software (gPROMS Model Builder Version 5.0) to simultaneously simulate the different sections composing the MBTSA (Mondino et al, 2017). The composite model was used to investigate the application of the MBTSA for CO 2 from a coal fired power plant.…”
Section: Introductionmentioning
confidence: 99%
“…The composite model was used to investigate the application of the MBTSA for CO 2 from a coal fired power plant. Based on the detailed model for the coal case (Mondino et al, 2017), the present work aims to give a more thorough assessment of the performance of an MBTSA process in the NGCC context. For this purpose, the configuration of the system is adapted to the NGCC case study, which differs from the coal fired power plant in terms of flue gas conditions (temperature, pressure, flow rate and composition).…”
Section: Introductionmentioning
confidence: 99%